Estimation of stepwise crack propagation in ceramic laminates with strong interfaces - L. Náhlík; K. Štegnerová; P. Hutar (Fracture and Structural Integrity)
During the last years many researchers put so much effort to design layered structures combining different materials in order to improve low fracture toughness and mechanical reliability of the ceramics. It has been proven, that an effective way is to create layered ceramics with strongly bonded interfaces. After the cooling process from the sintering temperature, due to the different coefficients of thermal expansion of individual constituents of the composite, significant internal residual stresses are developed within the layers. These stresses can change the crack behaviour. This results to the higher value of so-called apparent fracture toughness, i.e. higher resistance of the ceramic laminate to the crack propagation. The contribution deals with a description of the specific crack behaviour in the layered alumina-zirconia ceramic laminate. The main aim is to clarify crack behaviour in the compressive layer and provide computational tools for estimation of crack behaviour in the field of strong residual stresses. The crack propagation was investigated on the basis of linear elastic fracture mechanics. Fracture parameters were computed numerically and by author’s routines. Finite element models were developed in order to obtain a stress distribution in the laminate containing a crack and to simulate crack propagation. The sharp change of the crack propagation direction was estimated using Sih’s criterion based on the strain energy density factor. Estimated crack behaviour is qualitatively in a good agreement with experimental observations. Presented approach contributes to the better understanding of the toughening mechanism of ceramic laminates and can be advantageously used for design of new layered ceramic composites and for better prediction of their failure.